Antiviral activity of mx proteins from gilthead seabream (sparus aurata) against lymphocystis disease virus (LCDV). - Fernández-Trujillo, M. Alejandra; García-Rosado, Esther; Alonso-Sánchez, María del Carmen; Borrego-García, Juan José; Álvarez-Herrero, María del Carmen; Béjar-Alvarado, Julia (ELSEVIER, 2013)
Gilthead seabream (Sparus aurata), one of the most important fish species in the Mediterranean Aquaculture displays a high natural resistance to viral diseases. Until now, the main viral disease affecting gilthead seabream is the lymphocystis disease (LCD), caused by the lymphocystis disease virus (LCDV). LCDV is a DNA virus belonging to the Iridoviridae family. The predominant symptom of the disease is the presence of visible papiloma-like skin lesions. Although LCD is a self-limiting infection, it may cause high morbidity and, therefore, important economic losses for the industry. One of the main components of the immune system to fight viral infections is the interferon-mediated response. This cytokine is secreted by infected cells to promote an antiviral state in neighboring cells through the induction of several proteins, some of them with direct antiviral activity. One of these interferon-induced proteins with direct antiviral activity is the Mx protein. Our group has identified three Mx proteins in gilthead seabream, named SauMx1, SauMx2 and SauMx3. To evaluate their antiviral activity, three in vitro experimental systems were established, consisting in CHSE-214 cells stably expressing each Mx protein separately. In this study, the activity of these three Mx proteins has been tested against LCDV. Results showed that SauMx1 and SauMx2 have antiviral activity against this virus, as viral titers were reduced 96 fold and 856 fold for SauMx1 and SauMx2 respectively. In contrast, the presence of SauMx3 did not inhibit LCDV replication in the cells. As far as we know, this is the first description of a fish Mx protein with antiviral activity against LCDV. Thus, a deeper knowledge of this antiviral activity, and on the interactions taking place between gilthead seabream Mx proteins and LCDV, could help to design strategies against LCD.
Keywords: Virología; Peces - Genética - Aspectos inmunológicos; Gilthead seabream; Mx protein; LCDV; lymphocystis disease